Epidemiology, Clinical Characteristics, and Outcomes of Influenza-Associated Hospitalizations in US Children Over 9 Seasons Following the 2009 H1N1 Pandemic. (19th April 2022) - Kamidani, Satoshi; Garg, Shikha; Rolfes, Melissa A; Campbell, Angela P; Cummings, Charisse N; Haston, Julia C; Openo, Kyle P; Fawcett, Emily; Chai, Shua J; Herlihy, Rachel; Yousey-Hindes, Kimberly; Monroe, Maya L; et al.
Abstract: Background: Recent population-based data are limited regarding influenza-associated hospitalizations in US children. Methods: We identified children <18 years hospitalized with laboratory-confirmed influenza during 2010–2019 seasons, through the Centers for Disease Control and Prevention's Influenza Hospitalization Surveillance Network. Adjusted hospitalization and in-hospital mortality rates were calculated, and multivariable logistic regression was conducted to evaluate risk factors for pneumonia, intensive care unit (ICU) admission, mechanical ventilation, and death. Results: Over 9 seasons, adjusted influenza-associated hospitalization incidence rates ranged from 10 to 375 per 100 000 persons each season and were highest among infants <6 months old. Rates decreased with increasing age. The highest in-hospital mortality rates were observed in children <6 months old (0.73 per 100 000 persons). Over time, antiviral treatment significantly increased, from 56% to 85% ( P < .001), and influenza vaccination rates increased from 33% to 44% ( P = .003). Among the 13 235 hospitalized children, 2676 (20%) were admitted to the ICU, 2262 (17%) had pneumonia, 690 (5%) required mechanical ventilation, and 72 (0.5%) died during hospitalization. Compared with those <6 months of age, hospitalized children ≥13 years old had higher odds of pneumonia (adjusted odds ratio, 2.7 [95% confidence interval, 2.1–3.4], ICU admission (1.6 [1.3–1.9]), mechanical ventilation (1.6 [1.1–2.2]), and death (3.3 [1.2–9.3]). Conclusions: Hospitalization and death rates were greatest in younger children at the population level. Among hospitalized children, however, older children had a higher risk of severe outcomes. Continued efforts to prevent and attenuate influenza in children are needed. Abstract : During 2010–2019, 13 235 children were hospitalized with influenza. Adjusted hospitalization rates ranged from 10 to 375 per 100 000 persons each season and were highest among infants <6 months old. A substantial influenza burden was observed at all ages.